Translation of Cultural Aspects in Indonesian Folklore Nyai Anteh Sang Penunggu Bulan by Students of the German Department UM - Kezia Gracela Widya Lawalata; Rosyidah Rosyidah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2022)
This study aims to describe the translation of cultural aspects folklore "Nyai Anteh Sang Penunggu Bulan" as well as the ideology and the translation techniques carried out by the students of the German Literature Department, Faculty of Letters, Universitas Negeri Malang. This study uses qualitative method with source language text (SL) and target language text (TL) as the data sources. Meanwhile, the data of this study are in  form of SL words, phrases, and  sentences that contain cultural content and student translation versions. The data  was then analyzed interactively through three stages, namely data reduction, data presentation and conclusion drawing/verification. The results of this study indicate that the translation of cultural aspects in the folklore is classified into 5 cultural aspects as in the SL texts’ cultural aspects. Some aspects of the culture have been translated well by the students, while some are still not fully accepted. In translating the five cultural aspects, the students used the ideology of foreignization and domestication based on the needs of borrowing and literal translation techniques, even though the translation results are not always acceptable.